1997
DOI: 10.1016/s0014-5793(97)00838-7
|View full text |Cite
|
Sign up to set email alerts
|

Structural and functional characterisation of two proteolytic fragments of the bacterial protein toxin, pneumolysin

Abstract: Proteolytic cleavage of the bacterial protein toxin pneumolysin with protease K creates two fragments of 37 and 15 kDa. This paper describes the purification of these two fragments and their subsequent physical and biological characterisation. The larger fragment is directly involved in the cytolytic mechanism of this pore-forming protein, via membrane binding and self-association. The smaller fragment lacks ordered structure or discernible activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
(27 reference statements)
0
4
0
Order By: Relevance
“…4). One paper has also reported that the proteolytic cleavage of 142 amino acids from the N-terminus resulted in the loss of the cytolytic activity but not the binding to liposome containing cholesterol (20). These data indicated that truncation of N-terminal peptides did not affect the binding of domain 4 to cholesterol whereas it caused a significant reduction in the hemolytic activity.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…4). One paper has also reported that the proteolytic cleavage of 142 amino acids from the N-terminus resulted in the loss of the cytolytic activity but not the binding to liposome containing cholesterol (20). These data indicated that truncation of N-terminal peptides did not affect the binding of domain 4 to cholesterol whereas it caused a significant reduction in the hemolytic activity.…”
Section: Discussionmentioning
confidence: 97%
“…Domain 4 is distant from domain 1 and domain 3 and has been regarded as the site for binding to the membrane (14 -16, 19). Morgan et al reported that 37 kDa, 329 amino acid fragment obtained by proteolytic cleavage of PLY, which represented C-terminal part of PLY, was able to bind liposomes containing cholesterol (20). Iwamoto et al (21) and Tweten et al (22) reported that an inhibitory effect of C-terminal fragment of PFO on hemolysis by using a 196 amino acid fragment prepared by the proteolytic cleavage of full-length PFO.…”
Section: Discussionmentioning
confidence: 99%
“…Soluble PLY, in its monomeric state, has been shown by crystallographic methods to be an asymmetric molecule composed of 4 major domains (D1 to D4), including a-helices and b-sheets (Figure 2B). The N-terminal D1 domain, although not essential for cell binding, stabilizes overall protein structure and enables hemolytic activity (42,43). The non-contiguous D1 and D3 are adjacent in the 3D crystal structure and linked to the C-terminal of D4 via D2 (44) (Figure 2B).…”
Section: Mechanism Of Ply-mediated Membrane Permeabilizationmentioning
confidence: 99%
“…This microorganism is a leading cause of ill health and death worldwide, responsible for pneumococcal diseases such as pneumonia, meningitis, and sepsis ( Roth et al, 2018 ; Weiser et al, 2018 ). Pneumolysin and its derivatives are targets for the development of new vaccines ( Pichichero, 2017 ) and have long been produced and purified from Streptococcus pneumoniae and as recombinant proteins from Escherichia coli ( Mitchell et al, 1989 ; Paton et al, 1991 ; Morgan et al, 1997 ; Douce et al, 2010 ; Marshall et al, 2015 ; van Pee et al, 2017 ; Lee et al, 2018 ; Vorabyev et al, 2023 ). However, most publications are focused on the structural or immunological aspects of pneumolysin, rather than its process development.…”
Section: Introductionmentioning
confidence: 99%